Lazada Group - Aw Yong Chai Yee; Daisy Mui Hung Kee; Chen Xing; Pua Yin Qian; Siew Mei Qi; Ahmed Tariq Dehrab (Journal of International Conference Proceedings (JICP), 2019)
Lazada Group is a Southeast Asian e-commerce company founded in 2012 by Rocket Internet. Alibaba Group was bought Lazada’s controlling stake to support Alibaba's expansion plans in Southeast Asia in April 2016. The unwisely decision making was made the management of Lazada was not performing well. The controlling stake of Alibaba in Lazada has been led to a massive shake-up of the internal culture of Lazada. The people in Lazada may change in their behaviours, mentalities and attitudes along with the systems and processes that introduced by Alibaba Group even though the internal organization and structures are remaining the same. The dynamics of how people will change within the company will be interesting not only for the current employees themselves, but also ex-employees and long-serving customers.